Single-Nanometer-Sized Low-Valence Metal Hydroxide Crystals: Synthesis via Epoxide-Mediated Alkalinization and Assembly toward Functional Mesoporous Materials - Tarutani, Naoki (2016)
A study demonstrated a simple synthesis approach toward single-nanometer-sized crystals that work as nanobuilding blocks (NBBs) to form a great variety of mesoporous hydroxides and derived phases. The nanocrystals with diverse chemical compositions low-valence metal hydroxides, α-M(OH)2 (M = Mn(II), Fe(II), Co(II), Ni(II), and Cu(II)), and other (hydr)oxides composed of Al(III), Cr(III), Fe(III), Zr(IV), and Sn(IV)) were prepared in an aqueous ethanol solution. The nanocrystal formation was achieved by inducing a high supersaturation via the epoxidemediated alkalinization in a concentrated metal salt solution. A variety of carboxylic acids were used as growth controlling agents, permitting to finely control the size of low-valence metal hydroxide nanocrystals and to attain high stability against aggregation.